Exotoxin profiles of clinical isolates of Aeromonas hydrophila - Vadivelu, J.; Puthucheary, S.D.; Navaratnam, P. (Microbiology Society, 1991)
Eighty-six clinical isolates of Aeromonas hydrophila were studied for their ability to produce four exotoxins: a haemolysin active against rabbit erythrocytes, cytotoxin and enterotoxin detectable with Vero cell cultures, and the cholera toxin-like factor detected by an enzyme-linked immunosorbent assay. At least one exotoxin was produced by 80% of enteric and 96% of non-enteric isolates. The exotoxin profiles of non-enteric isolates were more restricted than those of enteric isolates, with haemolysin and cytotoxin producers preponderant. Although haemolysin and cytotoxin were produced by isolates from all sources, the enterotoxin and cholera toxin-like factor were more common amongst enteric isolates. The production of haemolysin and cytotoxin were closely related but the association between the enterotoxin and the cholera toxin-like factor was not significant.